Self-healing capacity of concrete - computer simulation study of unhydrated cement structure - He, Huan (Image analysis and stereology, 2007)
Aggregate occupies at least three-quarters of the volume of concrete, so its impact on concretećs properties is large. The aggregatećs influence on the non-hydrated part of the matured paste is assessed by concurrent algorithm-based computer simulation system SPACE in this paper. A distinction is made between interfacial zones (ITZs) and bulk paste. Containers with rigidboundaries were employed for the production of series of cement pastes. They were subjected to quantitative microstructure analysis. Relevant gradientstructures in the ITZ and bulk are presented and discussed. The relevance of this structure information for possible selfhealing of cracks is briefly discussed.
Keywords: Materiali, testiranje; Materials Testing; Computer Simulation; Slika, obdelava z računalnikom; Particle Size; Računalniška simulacija; Delec, velikost; Image Processing, Computer-Assisted; testiranje materialov